2007
DOI: 10.1007/s00464-007-9689-7
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a simulation center for surgical skills

Abstract: [No abstract available

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…This simulator has been developed through a joint effort of medical experts from the Balgrist University Hospital and the ETH Zurich. The aim of this new simulator is the presentation of a realistic virtual training environment, since other virtual reality simulators evaluated for training of knee arthroscopy [3, 4, 9, 11, 13–15, 23, 31, 33] only showed a marginal level of realism [7, 16, 17, 32]. Similar to other simulators, the simulator offers training of diagnostic and therapeutic arthroscopy and objective performance feedback.…”
Section: Introductionmentioning
confidence: 99%
“…This simulator has been developed through a joint effort of medical experts from the Balgrist University Hospital and the ETH Zurich. The aim of this new simulator is the presentation of a realistic virtual training environment, since other virtual reality simulators evaluated for training of knee arthroscopy [3, 4, 9, 11, 13–15, 23, 31, 33] only showed a marginal level of realism [7, 16, 17, 32]. Similar to other simulators, the simulator offers training of diagnostic and therapeutic arthroscopy and objective performance feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation has also been extensively studied in nursing education, with a recent meta-analysis demonstrating effectiveness with a range of learning objectives (Kim et al, 2016). HBSL has accordingly been endorsed by nursing professional bodies (National Council of State Boards of Nursing, 2005) and educators (Anderson, 2007;Haluck et al, 2007;Hammond, 2004;Hanberg, 2008;Henneman & Cunningham, 2005;McLaughlin et al, 2008). A recent analysis of several studies concluded that simulation is an effective training tool to improve the skills of professional registered nurses (Hegland et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However in eliminating an assistant, one effectively eliminates early exposure to laparoscopic procedures for junior doctors and surgeons, further eroding already scarce teaching and learning opportunities. In addition, many robotic assistants have been shown to be more expensive to implement (including cost of retraining surgeons and theatre staff) than the cost of using a junior to assist [2,3]. Furthermore, when considering the financial viability of any such device, one needs to factor in the often considerable operational costs (maintenance, consumables) of any robotic assistant [4], something that was absent from the article.…”
Section: To the Editormentioning
confidence: 99%
“…1 We suggest it would be more accurate to describe this support as a master-slave device. 2 Though we have highlighted some areas for consideration by the authors, we would like to congratulate the team on their endeavours and look forward to seeing how their device develops. …”
Section: To the Editormentioning
confidence: 99%